Кон Бранка Арсиќ (прир.), Жене, слике, измишљаји: Për Бранка Арсиќ (red.), Жене, слике, измишљаји - Angelovska, Despina; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2002)
Author(s): Despina Angelovska | Деспина Ангеловска Title (Macedonian): Кон Бранка Арсиќ (прир.), Жене, слике, измишљаји Title (Albanian): Për Бранка Арсиќ (red.), Жене, слике, измишљаји Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 173-174 Page Count: 2 Citation (Macedonian): Деспина Ангеловска, „Кон Бранка Арсиќ (прир.), Жене, слике, измишљаји“, Идентитети: списание за политика, род и култура, т. 1, бр. 2 (зима 2001): 173-174. Citation (Albanian): Despina Angelovska, „Për Branka Arsić (red.), Žene, slike, izmišljaji“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 2 (Winter 2002): 173-174.